Intelligent Irrigation System Using IoT For Aquaponics Application - Norazli, Muhammad Izzuddin; Abu Hassan, Omar; zohari, Mohd hakimi (Progress in Engineering Application and Technology, 2022)
Nowadays, everything in our daily life applying technology. Internet of Thing (IoT) is one of the modern technologies where we can monitor and control something from distance through internet. In this case, IoT are applied on the aquaponics application to fully monitor the water quality for the plant and fish to thrive. This research intends to automate the construct of an IoT-based prototype to monitor and gather parameter data in the Aquaponics ecology, including water level, humidity level, and temperature, thereby integrating the IoT Framework into Aquaponics. The method that are used is applying a few sensors that are TDS, temperature and pH and connect it to Node MCU esp8266 that act as a controller and send data to the Blynk application. As a result, the fish and plant can grow healthily because the quality of the water are being monitored through IoT application. In general, this research can save a lot of time and effort for farmer and hobbyist to operate the aquaponic system.